Internet Based Expert System for Hand Tractor Trouble Shooting - Mohammad Solahudin; Kudang Boro Seminar; Yuli Suharnoto (PERTETA, 2000)
The final step of this research was uploading the system in virtual FTP (File Transfer Protocol directory address /www/smipipb, and Uniform Resource Locator (URL) to access this site washttp://www.websamba.com/smipipb. The eveluation using the same browser engines indicutes that the system work as weN as in the local intranet. The knowledge base contains rules concerning the knowledge domain transformed and stored in the Microsoft Access data basejle. The main constribution of this research is to provide a multiuser software tool for hand tractor trouble shooting in the internet environment.